2014
DOI: 10.1177/0734904114563482
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of internal wall temperatures in enclosure fires

Abstract: Scaling of internal wall temperatures in enclosure fires The scaling of enclosure fires, including internal wall temperatures and heat fluxes, are thoroughly analyzed and a method of scaling internal wall temperatures is proposed. Two series of room fires were tested in three different scales, i.e. full scale (1:1), medium scale (1:2) and small scale (1:3.5), according to the theory. The fire source was either placed at the center or in the corner of the enclosures. The measured internal wall temperatures, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In addition to scaling the heat release rate of the burner, the need for scaling the time parameter was apparent as the thickness of the walls remained the same. The scaling of the time parameter was based on Quintiere [19] and on Li and Hertzberg, who scaled internal wall temperatures in enclosure fires [18]. Their study concluded that these scaling correlations presented a good agreement between the results from the scaled experiments and the large scale experiments within a number of different focus areas, including the HRR and the time parameter.…”
Section: ̇=̇+ ̇+ ̇+̇mentioning
confidence: 97%
“…In addition to scaling the heat release rate of the burner, the need for scaling the time parameter was apparent as the thickness of the walls remained the same. The scaling of the time parameter was based on Quintiere [19] and on Li and Hertzberg, who scaled internal wall temperatures in enclosure fires [18]. Their study concluded that these scaling correlations presented a good agreement between the results from the scaled experiments and the large scale experiments within a number of different focus areas, including the HRR and the time parameter.…”
Section: ̇=̇+ ̇+ ̇+̇mentioning
confidence: 97%
“…15 In particular, the gas burner HRR and the gas burner duration were scaled with, respectively, Equation (1) 16 and Equation (2). 16…”
Section: Froude Scaling Of the Gas Burner Hrr And Gas Burner Durationmentioning
confidence: 99%
“…To ensure that a correlation would exist across the scales, the Froude scaling technique was used to scale down the size of the fire with respect to the geometric scaling of the enclosure. 15 In particular, the gas burner HRR and the gas burner duration were scaled with, respectively, Equation (1) 16 and Equation (2). 16…”
Section: Froude Scaling Of the Gas Burner Hrr And Gas Burner Durationmentioning
confidence: 99%
“…The Froude scaling has been used widely in open and enclosure fires and results from model scale tests seem to fit full scale results well, see e.g. Li and Hertzberg's work [5]. Research on tunnel fires also shows there is a good agreement between model scale and full scale test results on many focused issues [14,15,[18][19][20][37][38][39].…”
Section: Froude Scalingmentioning
confidence: 99%
“…However, the scaling laws used for the thick insulating materials may not be accurate. Li and Hertzberg [5] conducted a scaling study of heat conduction and heat balance in a room fire. They carried out two series of room fire tests in three different scales where the aim was to investigate the scaling of temperatures inside the walls.…”
Section: Introductionmentioning
confidence: 99%